Gambaran Pelaksanaan Fungsi Perawatan Kesehatan Keluarga Di Wilayah Kerja Puskesmas Rumbai - Reni Zulfitri; Agrina '; Herlina ' (Fakultas Keperawatan, Universitas Riau, 2012)
The purpose of this research is to describe the family health care functions in the working area of Rumbai Public Health Center.The design used in this study was a descriptive exploratory. The number of samples in this study were 541 families who met theinclusion criteria by using multistage random sampling technique. The instrument applied was a questionnaire that has beendeclared valid and reliable. The results showed the number of families that could perform the family health care functions wasalmost the same compared to the number of families that could not. 51% families were carrying out the functions of familyhealth care. Thus, it is important for public health center nurses to educate families about health so that families can implementfamily health care functions at home, in order to reach an optimal degree of family health.Key word: family, functions, health care, health